2017
DOI: 10.1111/cob.12192
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of circulating microRNA levels in obese children compared to healthy controls

Abstract: As childhood obesity increases, it is becoming important to understand the complications of obesity in children and develop novel biomarkers. Evidence indicates that microRNAs (miRNA) are dys-regulated in obesity and may serve as sensitive and specific circulating biomarkers. Non-alcoholic fatty liver disease (NAFLD) is a complication of obesity that ultimately requires a liver biopsy to determine disease severity. While studies have been conducted in adults, no study to date has examined circulating miRNAs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…The most abundant miRNA in the liver is miR‐122, which accounts for more than half of the total hepatic miRNA content . Multiple studies have reported increased circulatory levels of miR‐122 in pediatric CLDs such as biliary atresia, CFLD, nonalcoholic fatty liver disease (NAFLD), and hepatitis B . Our study shows increased circulatory miR‐122 levels in children with CFLD when compared to both CFnoLD and healthy controls.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The most abundant miRNA in the liver is miR‐122, which accounts for more than half of the total hepatic miRNA content . Multiple studies have reported increased circulatory levels of miR‐122 in pediatric CLDs such as biliary atresia, CFLD, nonalcoholic fatty liver disease (NAFLD), and hepatitis B . Our study shows increased circulatory miR‐122 levels in children with CFLD when compared to both CFnoLD and healthy controls.…”
Section: Discussionmentioning
confidence: 54%
“…(31) Multiple studies have reported increased circulatory levels of miR-122 in pediatric CLDs such as biliary atresia, CFLD, nonalcoholic fatty liver disease (NAFLD), and hepatitis B. (17,(32)(33)(34) Our study shows increased circulatory miR-122 levels in children with CFLD when compared to both CFnoLD and healthy controls. We also found overexpression of miR-122 in CFnoLD compared to healthy controls.…”
Section: Discussionmentioning
confidence: 55%
“…The NAFLD‐associated changes in the spectrum of extracellular miRNA species present in human blood have been the subject of more than one intensive investigation . Each of these reports showed that circulating miRNAs reflect liver damage more precisely than do serum transaminases.…”
Section: Mirnas Are Proposed Both As Biomarkers and As Regulators Of mentioning
confidence: 99%
“…According to a very thorough RNA-Seq-based study by Hou et al, miR-122 is expressed almost exclusively in the liver, comprising more than 52% of the total pool of liver miRNAs (66). Overwhelming majority of published reports agree that the levels of miR-122 in sera of NAFLD individuals are elevated (53)(54)(55)(56)(57)(59)(60)(61)(62). If a majority of miRNAs present in circulation of individuals with NAFLD originate from the liver, it would be reasonable to expect an increase in the expression of miR-122 in hepatic parenchyma, along with a progression of NAFLD across its stages.…”
Section: Mir-122: Intracellular-extracellular Seesaw Expression Paradoxmentioning
confidence: 99%
See 1 more Smart Citation